Conceito de letramento: desafios e implicações no processo de aprendizado da língua materna - perspectiva bibliográfica - Ohde, Halide de Quadros (2015)
This dissertation falls within the research area of School Education: Pedagogical Theories and Practices. Its central theme is the concept of literacy within the initial learning of the mother tongue of schoolchildren. The origin of the dissertation is the results of previous research which conducted a survey of the occurrence of the concept of literacy. That particular study identified that the theoretical approaches used to support the concept of literacy were stable, with no major variations, and that they were encapsulated in the dichotomised view of the initial learning of the mother tongue and literacy. From that starting point, this MA dissertation set out to research the theoretical foundations of literacy used in PhD theses that have studied the process of learning the mother tongue, and to check if there has been progress in relation to the theoretical bases of those theses. Our hypothesis was that we would find in these theses greater reflection and new perspectives on the topic, which would go beyond the dichotomous view of the initial learning of the mother tongue and literacy. Consequently, this dissertation is characterised as a meta-search, which aimed to identify the theoretical foundations of literacy concepts, and to verify possible advances in academic discussions on this topic, within the PhD theses completed in 2002 2013, and which were available in the database of the Digital Library of Theses and Dissertations. For our analysis we used a theoretical framework based on studies on the subject by Geraldi, Kleiman, Tfouni, Soares, Ferreiro, Bakhtin, Freire and others. Our methodological approach was inspired by the perspective of content analysis, with the work of Laurence Bardin as a theoretical reference, since we chose to perform a study that categorised by data, developing a qualitative and quantitative analysis. The results point to the existence of academic research at the doctoral level involving the theme, and indicate a possible stabilisation of the theoretical bases of the initial learning of the mother tongue and literacy, indicating the dichotomy between both topics, as well as evidence of advances in relation to the idealist and humanist conception of literacy.